PENERAPAN MODEL PEMBELAJARAN OPEN ENDED UNTUK MENINGKATKAN HASIL BELAJAR ALJABAR LINIER MAHASISWA PENDIDIKAN MATEMATIKA DENGAN PEMBELAJARAN DARING - I Komang Sukendra; I Made Surat (Widyadari : Jurnal Pendidikan, 2021)
Online learning is a system of learning activities that are carried out without going through face-to-face directly but through the internet network. The purpose of this study was to determine the effect of applying the open-ended learning model with online learning in improving student learning outcomes and responses. This type of research is classroom action research. Action research is designed using two cycles, where each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The subjects of this study were students of the sixth semester of Mathematics Education, Universitas PGRI Mahadewa Indonesia, Academic Year 2020/2021. The object of research is student learning outcomes in Algebra subjects after being given learning using an open ended learning model with online learning. The results showed that the first cycle obtained an average grade of 77.96; 77.96% absorption, 66.67% classical completeness, and the second cycle obtained an average grade of 84.26, 84.26% absorption and 96.30% classical completeness. Conclusions from the results of action research (1) The application of the open-ended learning model with online learning can improve student learning outcomes, (2) There is a positive response from the sixth semester students of Mathematics Education at PGRI Mahadewa Indonesia University for the 2020/2021 Academic Year to the open-ended learning model with online learning at Linear Algebra course.